Dexamethasone Reduces Cell Adhesion and Migration of T47D Breast Cancer Cell Line - Mohammadi, Leila; Mosayyebi, Bashir; Imani, Mahsa; Rahmati, Mohammad (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Aberrant expression of cell adhesion molecules and matrix metalloproteinase (MMPs) plays a pivotal role in tumor biological processes, including progression and metastasis of cancer cells. Targeting these processes and acquiring a detailed understanding of their underlying molecular mechanism are an essential step in cancer treatment. Dexamethasone (Dex) is a type of synthetic corticosteroid hormone used as adjuvant therapy in combination with current cancer treatments such as chemotherapy in order to alleviate its side effects like acute nausea and vomiting. Recent evidences suggest that Dex may have antitumor characteristics. Objective: Dex affects the migration and adhesion of T47D breast cancer cells as well as cell adhesion molecules, e.g. cadherin and integrin, and MMPs by regulating the expression levels of associated genes. Methods: In this study, we evaluated the cytotoxicity of Dex on the T47D breast cancer cell line through MTT assay. Cell adhesion assay and wound healing assay were performed to determine the impact of Dex on cell adhesion and cell migration, respectively. Moreover, real-time PCR was used to measure the levels of α and β integrin, E-cadherin, N-cadherin, MMP-2, and MMP-9. Results: Dex decreased the viability of T47D cells in a time and dose-dependent manner. Cell adhesion and migration of T47D cells were reduced upon Dex treatment. The expressions of α and β integrin, E-cadherin, Ncadherin, MMP-2, and MMP-9 were altered in response to the Dex treatment. Conclusion: Our findings demonstrated that Dex may play a role in the prevention of metastasis in this cell line.
Keywords: dexamethasone